Phonetic-Form constraints in Arabic coordination - Jarrah, Marwan; Alrashdan, Imran; Al-Shawashreh, Ekab; Zuraikat, Malek J. (Lingua Posnaniensis, 2019)
This paper explores the use of bound forms in coordination constructions and ʔijjā and ʔijja in Modern Standard Arabic (MSA) and Jordanian Arabic (JA), respectively. Using the Minimalist Program (Chomsky 1995, 2000, 2005) as a theoretical framework, the paper proposes that the use of bound forms in such constructions is ruled by a Phonetic-Form constraint that prohibits cliticization of a bound form onto another bound form, i.e. the combination of two bound forms does not result in a free form; hence it is blocked. The paper demonstrates that the use of ʔijjā and ʔijja in MSA and JA, respectively, is a direct consequence of this constraint, so that ʔijjā/ʔijja is a Phonetic-Form object used to serve as a lexical host of bound forms (cf. Fassi Fehri 1993). The use of ʔijjā/ʔijja is also shown to be prosodically ruled; it is prosodically dependent so that ʔijjā/ ʔijja should be a member of the prosodic unit which also includes the preceding word.